Teoria das pulsões e as relações de objeto: Ronald Fairbairn critica Sigmund Freud - Zweifel, Juliana Imthon (2022)
This work is a historical and metapsychological approach to the first steps of object relations theory developed by William Ronald Dodds Fairbairn to criticize the drive theory developed by Sigmund Freud. For a better understanding of the concept of drive, an analysis is made of its development, the applications of the German word Trieb, its uses in Sigmund´s Freud´s native language and in Portuguese and its transformations throughout Freud´s teaching. A brief biography of Ronald Fairbairn is presented, as well as a description and analysis of the theories developed by Fairbairn in the 1940s, in particular the libido theory, the development theory and the endopsychic structure considered in terms of object-relationships he developed. Some limitations of the theory developed by Fairbairn and points of contact between it and the Freudian drive theory are pointed out